E Hine: Talking about Māori teen pregnancy with government groups. (December 2016) - Adcock, Anna; Lawton, Beverley; Cram, Fiona
Despite improved access to health services in Aotearoa New Zealand there remains a significant socio-economic and health gap between Māori (Indigenous New Zealanders) and Pākehā (non-Māori). E Hine (Girl) is a qualitative Kaupapa Māori (by Māori, for Māori) research project seeking to identify barriers and facilitators to positive health outcomes for young Māori mothers (under 20 years) and their infants. We present the findings of a discourse analysis of six semi-structured interviews with 13 representatives from six government agencies who were asked how their agency catered to the needs of young Māori mothers. Interviews were conducted in Wellington in 2013. First, we discuss respondents' perspectives on how their agencies work to increase positive health outcomes. Next, we discuss structural issues, such as resource distribution, organization, and "silence", that may act as barriers to positive outcomes. Addressing these barriers is essential to successfully deliver policies and initiatives that meet the needs of young Māori mothers and their infants.